The Veil: Women Writers on Its History, Lore, and Politics By Jennifer Heath, editor (Berkeley: University of California Press, 2008. 346 pages.) (American Journal of Islam and Society, 2009)
Taking an expansive notion of what is a “veil” and recognizing its immemorialrelationship to sacredness, Jennifer Heath has put together a wonderfulcollection of essays about it. The twenty-one female contributors considerthe veil from a variety of viewpoints: academic, personal memoir, and artistic.Her introduction and epilogue presents the book’s overall goal and asummation. The main argument is that “the veil” has been (and will remain)part of human society, in countless cultures and religions, for thousands ofyears. It can be a piece of cloth, a mask, or even related to the mystery of nature (as in the ancient Greek goddess Nyx [Night], drawing the veil ofdarkness across earth, while Selene [Moon] rises wearing a veil [p. 5].).”Current debates over veiling focus only on Islamic veiling and its relationshipto women’s oppression, which politicizes and narrows the understandingof this practice.There is no singular truth to “the veil,” Heath suggests, and that is preciselythe feeling one gets, for after reading the entire collection, one is nowiser to “the” meaning of “the” veil. The “truth” of the veil, rather, is thatthe current debate over it (does it or does it not oppress women?) detractsfrom the real issues women face: ...